The mediating role of self-continuity on the link between childhood adversity and loneliness in later life - Lampraki, Charikleia; Jopp, Daniela S.; Spini, Dario (Frontiers in Psychology, 2022)
Many factors may influence adaptation to critical life events such as divorce and bereavement in the second half of life, including having faced childhood adversity. However, pathways to reduced adaptation success are poorly understood. Self-continuity, an identity mechanism that incorporates life changes into a coherent life story, may contribute to better adaptation to adult critical life events, such as feeling less socially and emotionally lonely. We investigated the mediating role of self-continuity channelling the effects of childhood adversity on later life adaptation outcomes among individuals who had experienced divorce or bereavement. Data were derived from the longitudinal LIVES Intimate Partner Loss Study conducted in Switzerland from 2012 to 2016. The sample consisted of individuals who had experienced divorce (n = 416, Mage = 57.35) or bereavement (n = 339, Mage = 71.36) in later life, and a continuously married control group (n = 925, Mage = 67.04). Multilevel moderated mediations were used. Self-continuity mediated the effect of childhood adversity on emotional loneliness for all marital groups, but to a greater extent among divorcees. Self-continuity also mediated the effect of childhood adversity on social loneliness; however, this effect did not differ by marital group. In conclusion, childhood adversity is associated to greater loneliness in later life through self-continuity. Divorcees are the most impacted group regarding emotional loneliness, as they experience lower levels of self-continuity. Interventions that aim to reinforce self-continuity may help overcome social and emotional loneliness, especially for individuals who have experienced the loss of their partner through divorce.